Influence of Neonatal Practice Variation on Outcomes of Late Preterm Birth - Aliaga, Sofia; Boggess, Kim; Ivester, Thomas S.; Price, Wayne A. (American Journal of Perinatology, 2014)
Objective Examine variation in short-term outcomes of late preterm births (340/7–366/7 weeks) between a university teaching hospital, teaching community hospital, and nonteaching community hospital.Study Design Review of maternal and newborn data from a random sample of late preterm births at three hospitals in North Carolina from 2008 to 2009. Outcomes included length of stay, neonatal intensive care unit (NICU) admission, respiratory support, antibiotic exposure, phototherapy exposure, and hypoglycemia.Results We analyzed data from 331 singleton late preterm newborns: 93 (28.1%) from a university teaching hospital, 110 (33.2%) from a teaching community hospital, and 128 (38.7%) from a nonteaching community hospital. Mean gestational age did not vary between hospitals. NICU admission, exposure to antibiotics, and phototherapy were more common at the university teaching hospital after controlling for risk factors, yet length of stay was shortest at the university teaching hospital and longest at the teaching community hospital after adjustment.Conclusion Practice variation contributes to differences in length of stay, NICU admission, and exposure to antibiotics and phototherapy among late preterm newborns. Differences in practice during the birth hospitalization may affect outcomes and health care utilization (e.g., readmission) after discharge.
Keywords: late preterm; practice variation; neonatal care